Tinjauan Terhadap Relevansi Hukuman Pidana dalam Sistem Peradilan Modern - Afinda Wahyu Nur Sholikhah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research conducts an in-depth review of the relevance of criminal punishment in the context of the modern justice system. By analyzing the evolution of criminal punishment and the development of the justice system, this research aims to evaluate the extent to which criminal punishment still has relevance in achieving the goals of a quality justice system. Research methods involve literature analysis, case studies, and interviews with legal experts. Research findings highlight the complexity of the interplay between criminal punishment, law enforcement, and rehabilitation goals. There is a tension between the emphasis on punishment as a deterrent and the need to create a more progressive and rehabilitative system. The results of the analysis also show that there is an imbalance in the application of punishment, especially related to social and economic factors. The research conclusions propose a critical consideration of the sustainability of criminal punishment in the modern justice system. This research suggests the need for a more comprehensive policy review and reform, including a more holistic approach to law enforcement and community development. The results of this research contribute to a better understanding of the role of criminal punishment in achieving justice in the modern judicial era.